An Attempt to Synthesize 2-(2’,4’Dibromophenoxy) Anisole - Aanchal (My University, 2017)
Poly brominated diphenyl ethers (PBDEs) are used as flame retarding materials in many consumer products. Many other PBDEs that are obtained from marine sources show biological activities like antibacterial, antifungal and antifouling. Most of PBDEs have been isolated from sponges of Dysidea species. This work attempts to synthesize a PBDE, 2-(2’, 4’-Dibromophenoxy) anisole (1), using three steps. The nucleophilic aromatic substitution of 2, 4-dinitroflourobenzene with methoxy phenol (Guai acol) gave 2-(2’, 4’-Dinitrophenoxy)anisole (3) which upon reduction with 5% palladium on charcoal gave 2-(2’, 4’-Diaminophenoxy) anisole (2). The diazotisation reaction of the synthesized amine (2) using t-butyl nitrite, CuBr2 in anhydrous acetonitrile was expected to yield compound 1. All the synthesized compounds were purified by column chromatography and analyzed by 1H and 13 C NMR.
Keywords: PBDE congeners; Lamellodysidea herbacea; Antibacterial; antifungal; IC50; MIC